Setting Them Up To Fail - David Allan (PRISM)
This paper looks at post-16 progression opportunities for a group of previously disaffected 14–16-year-old students who undertook vocational learning in their final two years at school in the north-west of England. The paper argues that advanced forms of vocational learning at key stage 4 are leading to over-skilling and educational limbo for many young people. Questionnaire data was obtained from 109 participants in total. These included 16-21-year-olds looking to enter further education or employment with training (n=84), 14 vocational learning tutors, and 11 further education teachers. Although the vocational route can lead to a nationally recognised qualification, literacy and numeracy achievements are often below the expected standard, thus creating a mismatch in identified abilities. Due to the current government-enforced pressure to succeed in English and maths, a perceived ‘deficiency’ in any of these areas presents a significant barrier to progression. The students in this study are seen to be vocationally over-skilled yet underachieving in academic areas. As such, progression routes are severely limited, resulting in a high number of individuals dropping out of learning altogether.